If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 5 + 3(7x + -1) Reorder the terms: 2 = 5 + 3(-1 + 7x) 2 = 5 + (-1 * 3 + 7x * 3) 2 = 5 + (-3 + 21x) Combine like terms: 5 + -3 = 2 2 = 2 + 21x Add '-2' to each side of the equation. 2 + -2 = 2 + -2 + 21x Combine like terms: 2 + -2 = 0 0 = 2 + -2 + 21x Combine like terms: 2 + -2 = 0 0 = 0 + 21x 0 = 21x Solving 0 = 21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21x' to each side of the equation. 0 + -21x = 21x + -21x Remove the zero: -21x = 21x + -21x Combine like terms: 21x + -21x = 0 -21x = 0 Divide each side by '-21'. x = 0 Simplifying x = 0
| X^2=x^2+x-20 | | 1/2v-1/5=-2/3 | | Qxs=-340+10Px | | 52x-52x-6-6= | | (3/8)*45= | | 0.45/ln | | 14x+4x+2x-10x=20 | | 36=w-12 | | X-3y+2x+4= | | (5/8)*45= | | -y-6-3y-y= | | 14=5p+9p | | 19=5+3(7w+3) | | x^3+x^2-x-x-9=0 | | 2q+8q=90 | | 20=10(y-9) | | 18y-6+15y= | | 12=4z+2z | | 2sin(5x)cos(5x)=0 | | 54=8a+10a | | 48=4q+8q | | y=19x-16x | | 90=10w+8w | | 10=5(b-10) | | 10(x-2)-(x-4)= | | 3x^3+4x^2+6x=0 | | 5r+4r=90 | | 73=10r+3 | | 3y-2+34=360 | | X(3y-2z+9)= | | 6+5c=36 | | 9+3[2-13(x-1)]=21-18x |